(untitled) (Contemporary Mathematics, 2023)
The key objective of the present study is to elaborate the concept of boundary layer flow and heat transfer of magnetohydrodynamics namely Cu-water nanofluid flow towards an exponentially shrinking sheet with aid of mathematical modeling and computation. The present mathematical model is investigated under the influence of thermal radiation and suction. Using exponential form of similarity variables, the system of partial differential equations (PDEs) are converted in to a set of ordinary differential equations (ODEs). The resulting nonlinear ODEs are computationally solved by using a two-point boundary value problem numerical technique, which constitutes with common finite difference method. The influence of physical parameters such as magnetic field parameter, Eckert number, suction parameter, radiation parameter are described in details with the help of graphical demonstration of velocity and temperature distributions, coefficient of skin fiction and rate of heat transfer. Computational results reveal that after suspension of nanoparticles into base fluid as water fluid temperature raised significantly compare to that of pure fluid. It is also observed that for rising values of magnetic field parameter, thermal radiation, particles volume fraction fluid temperature distribution significantly improved; whereas opposite phenomena is true for suction parameter and Prandtl number. The rate of heat transfer accelerated with Eckert number, Prandtl number, while coefficient of skin friction boost with thermal radiation parameter. For verifying purposes, a comparison has been shown between present results and the computational results of previous studies and found a very close agreement.